(untitled) (Heritage, 2024)
Since the French Revolution in 1789, the nobility has ceased to be the ruling class in society. Since then, nobles began to use only certain privileges: the use of a noble title, the use of a coat of arms, an epithet, the right to join certain knightly orders and other rights. In the area of ​​Croatia, Slavonia and Vojvodina, nobility could be acquired in various ways: royal donation, coat of arms, perfection, adoption and indigence. Among those who received nobility were various professions: accountants, judges, veterinarians, doctors, pharmacists, merchants, officers and other professions. It is little known that some postmen also received nobility for certain services they rendered to the state. These four families, which we describe in this paper, were among the postmen. These are the families: Haraminčić, Andrejević, Oršić and Zitar. For each family, according to international methodology, we provide the time when they received the nobility, who received the nobility, the occupation of the recipient of the nobility and brief biographical information. We also bring a picture of the coat of arms for each family.